1986
DOI: 10.1212/wnl.36.7.879
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography in Alzheimer's disease

Abstract: Twenty-one patients with a clinical diagnosis of dementia of the Alzheimer's type (DAT) and 29 healthy, age-matched controls were studied using positron emission tomography (PET) and [18F]2-fluoro-2-deoxy-D-glucose to measure regional cerebral glucose consumption in the resting state. Reductions in ratio measures of relative metabolism in some parietal, temporal, and frontal regions were found in mild, moderate, and severe DAT groups. A significant increase in right/left metabolic asymmetry, particularly in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
156
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(181 citation statements)
references
References 0 publications
22
156
0
3
Order By: Relevance
“…Older adults with the ε4 allele who engaged in more physical activity had greater memory-related activation in posterior temporal and parietal regions than non ε4-carriers or those with lower physical activity. This result is particularly interesting as these areas are some of the first regions of cortex to show metabolic deficits in early AD [169][170][171] . This work shows interesting influences of both APOE genotype and physical activity on memory-related brain activation in cognitively intact but genetically at-risk older adults, but it is not clear if this increase is compensatory or protective against future cognitive decline.…”
Section: Risk Factors For Alzheimer's Disease: Apoementioning
confidence: 87%
“…Older adults with the ε4 allele who engaged in more physical activity had greater memory-related activation in posterior temporal and parietal regions than non ε4-carriers or those with lower physical activity. This result is particularly interesting as these areas are some of the first regions of cortex to show metabolic deficits in early AD [169][170][171] . This work shows interesting influences of both APOE genotype and physical activity on memory-related brain activation in cognitively intact but genetically at-risk older adults, but it is not clear if this increase is compensatory or protective against future cognitive decline.…”
Section: Risk Factors For Alzheimer's Disease: Apoementioning
confidence: 87%
“…Marked declines in cerebral glucose metabolism are associated with Alzheimer's disease, especially in the parietal and temporal cortices (28,29,37,54). Initial studies by Kalaria and Harik (59) demonstrated a reduction in the 55-kDa form of GLUT1 in cerebral microvessels prepared from Alzheimer's patients compared with normal age-matched controls (60).…”
Section: Neuronal Glut3 and Cerebral Glucose Utilizationmentioning
confidence: 99%
“…Whereas there is general agreement that AD typi cally shows defects of perfusion and metabolism in the parietal cortex (Foster et aI., 1983;Duara et al , 1986;Deutsch and Tweedy, 1987;Jagust et aI., 1987), local alterations in metabolism and blood flow have not been consistently observed in PD. Since parkinsonism results from degeneration of the dopaminergic nigrostriatal neurons (Hornykiewicz, 1966), one would expect that dopamine depletion within the basal ganglia might result in consistent alterations of local functional activity and, conse quently, of rCMR and rCBF.…”
Section: S101mentioning
confidence: 99%